Global loss of avian evolutionary uniqueness in urban areas - Ibáñez-Álamo, Juan Diego; Rubio, Enrique; Benedetti, Yanina; Morelli, Federico (Global change biology, 2017)
Urbanization, one of the most important anthropogenic impacts on Earth, is rapidly expanding worldwide. This expansion of urban land-covered areas is known to significantly reduce different components of biodiversity. However, the global evidence for this effect is mainly focused on a single diversity measure (species richness) with a few local or regional studies also supporting reductions in functional diversity. We have used birds, an important ecological group that has been used as surrogate for other animals, to investigate the hypothesis that urbanization reduces the global taxonomical and/or evolutionary diversity. We have also explored whether there is evidence supporting that urban bird communities are evolutionarily homogenized worldwide in comparison with nonurban ones by means of using evolutionary distinctiveness (how unique are the species) of bird communities. To our knowledge, this is the first attempt to quantify the effect of urbanization in more than one single diversity measure as well as the first time to look for associations between urbanization and phylogenetic diversity at a large spatial scale. Our findings show a strong and globally consistent reduction in taxonomic diversity in urban areas, which is also synchronized with the evolutionary homogenization of urban bird communities. Despite our general patterns, we found some regional differences in the intensity of the effect of cities on bird species richness or evolutionary distinctiveness, suggesting that conservation efforts should be adapted locally. Our findings might be useful for conservationists and policymakers to minimize the impact of urban development on Earth's biodiversity and help design more realistic conservation strategies.
Keywords: zvířata; fylogeneze; Animals; ptáci; Urbanization; velkoměsta; Biodiversity; Cities; urbanizace; Phylogeny; Conservation of Natural Resources; zachování přírodních zdrojů; biodiverzita; Birds